2013
DOI: 10.7600/jpfsm.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryotherapy on joint position sense and intraarticular blood flow volume in healthy knee joints

Abstract: The purpose of this study was to investigate the influence of cryotherapy on knee joint position sense (JPS) and intraarticular blood flow volume (IBFV) and evaluate their relationships with cooling time as well as with surface temperature and deep temperature. Ten healthy volunteers were examined. This study consisted of a same-subjects repeated-measures design, with the timeframe of cryotherapy application (no therapy [resting control group], 2-min cooling, or 15-min cooling intervention) after exercise bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Regarding the knee joint, five articles were found to perform this analysis. In four of these investigations, the evaluation of the moment over time is performed only once, after 15/20 min [ 19 , 22 , 33 , 34 ]. The other study performs measurements after 5, 10, 15, 20, 25, and 30 min of cryotherapy application [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the knee joint, five articles were found to perform this analysis. In four of these investigations, the evaluation of the moment over time is performed only once, after 15/20 min [ 19 , 22 , 33 , 34 ]. The other study performs measurements after 5, 10, 15, 20, 25, and 30 min of cryotherapy application [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other study performs measurements after 5, 10, 15, 20, 25, and 30 min of cryotherapy application [ 32 ]. In three of these investigations [ 32 , 33 , 34 ], the authors concluded that the application of ice significantly interferes with the individuals’ proprioception. Regarding the ankle joint, two studies were found that make a temporal analysis of the effect of ice [ 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation